2011
DOI: 10.1158/1078-0432.ccr-11-0479
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Apoptotic Signaling Characteristics of the Anti-CD40 Monoclonal Antibody Dacetuzumab and Rituximab Produce Enhanced Antitumor Activity in Non-Hodgkin Lymphoma

Abstract: Purpose: Individually targeting B-cell antigens with monoclonal antibody therapeutics has improved the treatment of non-Hodgkin lymphoma (NHL). We examined if the antitumor activity of rituximab, CD20-specific antibody, could be improved by simultaneously targeting CD40 with the humanized monoclonal antibody dacetuzumab (SGN-40).Experimental Design: Dacetuzumab was dosed with rituximab to determine the in vivo activity of this combination in a subcutaneous Ramos xenograft model of non-Hodgkin lymphoma (NHL). T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…More directly human trimeric CD154 can induce apoptosis of CD40-expressing solid tumors (46). Finally the CD40 agonist antibody dacetuzumab is used to treat metastatic melanomas and B cell lymphomas by inducing apoptosis (49, 50). Thus the ability to induce CD154-dependent CD4 CTLs by vaccination with an adjuvanted protein may be of particular benefit for therapeutic cancer vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…More directly human trimeric CD154 can induce apoptosis of CD40-expressing solid tumors (46). Finally the CD40 agonist antibody dacetuzumab is used to treat metastatic melanomas and B cell lymphomas by inducing apoptosis (49, 50). Thus the ability to induce CD154-dependent CD4 CTLs by vaccination with an adjuvanted protein may be of particular benefit for therapeutic cancer vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Dacetuzumab (SGN-40) is a partial agonist antibody to CD40 that demonstrated preclinical additive to synergistic effects in combination with rituximab in NHL cell line and mouse models (Lewis et al , 2011). A dose-escalation phase I trial of dacetuzumab in patients with relapsed/refractory B-cell NHL reported an ORR of 12%.…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of CD40 has led to the development of CD40-directed therapies that range in activity from agonists to antagonists (Schoenberger et al , 1998; Advani et al , 2009; Lewis et al , 2011). Lucatumumab is a fully human antagonistic anti-CD40 mAb.…”
mentioning
confidence: 99%
“…In vitro and in vivo experiments have shown that dacetuzumab in combination with rituximab, a chimeric anti-CD20 mAb, induced an enhanced antitumor activity as compared to each agent alone [111]. By activating different mechanisms whereby dacetuzumab upregulated the proapoptotic p53 family member, Tap63a, and Fas, and rituximab abrogated the dacetuzumab-induced expression of the oncoprotein, BCL-xL, both immunotherapeutic agents were complementary to each other, and their combination induced an enhanced anti-tumorigenic response [111]. Interestingly, a physical and functional association has been recently reported between CD40 and CD20 on cell surface, leading to upregulated CD20-and CD40-mediated cell death responses upon stimulation with their respective antibodies.…”
Section: Combination Therapies Involving Anti-cd40 Absmentioning
confidence: 99%